New generalized Nadarajah-Haghighi distributions in survival analysis - PEÑA RAMÍREZ, Fernando Arturo (2017)
The interest in developing new continuous distributions a remain important in statistical analysis. This topic is also important in survival analysis and has been used in many applications in fields like biological sciences, economics, engineering, physics, social sciences, among others. One reason is that the time of life or survival time is a random variable which can take constant, decreasing, increasing, upside-down bathtub (unimodal) and bathtub-shaped hazard rate functions. These new models can be defined by adding parameters to an existing distribution and considering the compounding approach, among other techniques. In this thesis, we consider these methods to propose four new continuous distributions, namely the exponentiated generalized power Weibull, Nadarajah-Haghighi Lindley, Weibull Nadarajah-Haghighi and logistic Nadarajah-Haghighi distributions. We provide a comprehensive mathematical and statistical treatment of these distributions and illustrate their flexibility through applications to real data sets. They are useful alternatives to other classical lifetime models.